Coastal Vulnerability Index Modeling for Western Coast of Pangandaran - Ruzana Dhiauddin; Wisnu Arya Gemilang; Koko Ondara; Uung Jantama Wisha; Guntur Adhi Rahmawan; Gunardi Kusumah (Jurnal Segara, 2019)
Western coast of Pangandaran Sub-district became a popular destination either for domestic or international tourists since it offers many attractive activities and is supported by plenty of hotels, homestays, restaurants and other facilities. However, those advantages were not related with environmental condition, which is characterized by erosional features and dilapidated semi-permanent buildings in several areas with insufficient numbers of coastal protection structures. The combination of poor protection in highly exploited beach pose a threat to local residents, tourists and also the environment. This study is aimed to assess the risk that is faced by Pangandaran Bay. We apply vulnerability assessment in western coast of Pangandaran by integrating two methods: Smartline and CVI (Coastline Vulnerability Index). The result shows the coastal vulnerability index for the study area ranges from 16.43 to 129.9 that are classified into 5 categories; 1) Very low (0.4 km, Sodonglandak Headland - Parigi Bay), 2) Low (0.7 km of Parigi Bay), 3) Moderate (1.2 km, west - east part of Parigi Bay), 4) High (0.3 km, south of Pangandaran Village), and 5) Very High (2.1 km, Pangandaran Village - Pananjung Village). The result of this study is imperative for local governments and stakeholders as a basis for further coastal developments in the western coast of Pangandaran in term of tourism.